The biology of mangroves - Hogarth, Peter J. (Oxford University Press, 1999)
Mangroves and seagrasses form extensive and highly productive ecosystems that are biologically diverse and economically valuable. This new edition has been thoroughly revised and updated to provide a comprehensive introduction to all aspects of the biology and ecology of mangroves and seagrasses, using a global range of examples. It deals with the adaptations of these plants to their exacting environment, the rich and diverse communities of organisms that depend on mangrove forests and seagrass meadows (including tree-climbing shrimps, synchronously flashing fireflies and 'gardening' seacows), the links between mangrove, seagrass, and other habitats, the evolution, biodiversity and biogeography of mangroves and seagrasses, and the likely effects of global climate change. The economic value of mangroves and seagrasses is also discussed, including approaches to rational management of these vital resources, and techniques for the restoration of degraded habitats. As with other titles in the Biology of Habitats Series, particular emphasis is placed on the organisms that dominate these aquatic environments although pollution, conservation and experimental aspects are also considered. The book is intended for students, naturalists and professionals and assumes no previous knowledge of mangrove or seagrass ecology.